Transforming the means-end chain model of the QFD into interconnected hierarchical network structures for sustainable product design - Lanndon Ocampo; Ammabelle Marie Jumao-as; John James Labrador; Alona Mae Rama (International Journal of Sustainable Engineering, 2021)
Various extensions of the environmentally-conscious quality function deployment (QFD) were explored to address sustainable product design. To provide a systematic computational platform, the integration of fuzzy set theory and multiple criteria decision making (MCDM) methods becomes a popular approach. However, most applications of the fuzzy QFD-MCDM approaches are concentrated on the product planning phase, which limits overall sustainability considerations in the remaining design phases. Thus, this work adopts the means-end chain (MEC) model of the QFD, along with the sustainability agenda of the stakeholders. Succinctly, the proposed framework transforms the MEC model into a series of interconnected hierarchical networks, and each network representing a phase is translated into a supermatrix of the analytic network process (ANP). The fuzzy analytic hierarchy process (AHP) and fuzzy decision-making trial and evaluation laboratory (DEMATEL) are used to populate the supermatrix. To demonstrate its efficacy, an actual case study of vegetable cooking oil is reported in this work. The findings illustrate the capability of the proposed framework in translating the sustainability agenda into insights in the design phases. This consistency of information flow allows stronger associations of the design parameters, ensuring communication of sustainability agenda across phases. The limitations and managerial implications are also discussed.